I'm trying to prove the below equation, where $ a,b \in G $ and $(G, *) $ is a group.

$(a*b)^{-1} = (a^{-1}) * (b^{-1}) $

I'm not really sure how to do it though. I tried doing something like

$(a*b)^{-1} * (a*b) = e = a * a^{-1} * b^{-1} * b $

$(a*b)^{-1} * (a*b) = e = a * (a^{-1} * b^{-1}) * b $

However, I can't get the RHS to $ (a * b)* (a^{-1} * b^{-1}) $ without assuming communitivity.

How would I go about doing this? Any help is appreciated.


Edit: Given that correction, would this be correct?

$ (a*b)^{-1} * (a*b) = e = a*(b*b^{-1})*a^{-1}$


$ a*(b*b^{-1})*a^{-1} = a*b* (b^{-1}*a^{-1}) = (a*b)*(b^{-1}*a^{-1})$


$ (a*b)^{-1} = (b^{-1}*a^{-1})$

  • 8
    $\begingroup$ This isn't true, unless you actually have commutativity. The statement that holds is $(a*b)^{-1}=b^{-1}a^{-1}$. $\endgroup$ Commented Aug 21, 2012 at 4:31
  • 1
    $\begingroup$ Thanks, is my edited version correct? $\endgroup$ Commented Aug 21, 2012 at 4:50

4 Answers 4


Most of the answers above tell you how to verify what $(a \ast b)^{-1}$ is once you have found it. Of course this is all very well and good if you "already know the answer", but gives no insight in how "you find the answer". But this is group theory, and groups are in a sense "designed for solving equations". So let's write an equation and solve it.

An inverse for $a \ast b$ is an element $x \in G$ such that:

$(a \ast b) \ast x = e = x \ast (a \ast b)$. Therefore (using the first equation):

$a^{-1} \ast ((a \ast b) \ast x) = a^{-1} \ast e$

$(a^{-1} \ast a) \ast (b \ast x) = a^{-1}$

$e \ast (b \ast x) = a^{-1}$

$b \ast x = a^{-1}$

$b^{-1} \ast (b \ast x) = b^{-1} \ast a^{-1}$

$(b^{-1} \ast b) \ast x = b^{-1} \ast a^{-1}$

$e \ast x = b^{-1} \ast a^{-1}$

$x = b^{-1} \ast a^{-1}$

Having found what any "right-inverse" of $a \ast b$ must be, and since $G$ is a group, it must be that $x$ is also a left-inverse, although it may now be verified directly that $b^{-1} \ast a^{-1}$ is also a left inverse.


The problem is that what you are trying to prove is false. The correct statement is $ (a * b )^{-1} = b^{-1} * a^{-1}.$

  • $\begingroup$ Thanks for the reply, is my edited post correct? $\endgroup$ Commented Aug 21, 2012 at 4:43
  • $\begingroup$ @user1520427 It seems to take a very difficult path. It is easy to check if something is indeed the inverse of another element: Y is the inverse of X if XY=YX=e. $\endgroup$ Commented Aug 21, 2012 at 4:58
  • $\begingroup$ I was trying to do the derivation of it, not just check that it's true. I guess my wording was a bit ambiguous. $\endgroup$ Commented Aug 21, 2012 at 7:27

To show that $(a\star b)^{-1} = b^{-1}\star a^{-1}$, all you need to do is multiply $a\star b$ and $b^{-1}\star a^{-1}$ and see that they are inverses of one another:

$$\begin{eqnarray} (a\star b)\star( b^{-1}\star a^{-1}) & = & \\ a\star ((b\star b^{-1})\star a^{-1}) & = & \\ a\star (e\star a^{-1}) & = & \\ a\star a^{-1} & = & e \end{eqnarray}$$

so $b^{-1}\star a^{-1}$ is the inverse of $(a\star b)$.


Assuming your post should be prove $(a*b)^{-1}=b^{-1}*a^{-1}$ for $a,b \in G$ where $(G,*)$ is a group.

Then by definition of inverses $(a*b)*(a*b)^{-1}=e$. Then using left inverse and associative properties we can get the following:

$(a*b)*(a*b)^{-1}=e \implies a^{-1}*(a*b)*(a*b)^{-1}=a^{-1}*e \implies (a^{-1}*a)*b*(a*b)^{-1}=a^{-1} \implies e*b*(a*b)^{-1}=a^{-1} \implies b*(a*b)^{-1}=a^{-1}$

Now use left inverses and associative properties again with $b$ and you'll get the desired result of $(a*b)^{-1}=b^{-1}*a^{-1}$.


You must log in to answer this question.

Not the answer you're looking for? Browse other questions tagged .